Prevalence of Bartonella henselae in Italian Stray Cats: Evaluation of Serology To Assess the Risk of Transmission of Bartonella to Humans - Fabbi, Massimo (American Society for Microbiology, 2004)
Bartonella henselae is the major etiological agent of cat scratch disease in humans. Cats act as the natural reservoir of B. henselae and can transmit the infection to humans by a bite or scratch. The prevalence of B. henselae in cat populations was evaluated by serological and bacteriological tests. A total of 769 stray cats from three urban and three rural areas in northern Italy were sampled between January 1999 and December 2000. The positive and the negative predictive values of serological tests with respect to bacteremic status were evaluated. Tests of a total of 140 cats (18%) resulted in detection of bacteremia. A total of 540 cats were tested by serology; 207 (38%) were seropositive. Of the 531 cats tested by both methods, the results for 65 (12.2%) showed both bacteremia detection and seropositivity. The molecular typing of the isolates showed that 20.6% of bacteremic cats were infected with B. henselae type I strain, 61.1% were infected with B. henselae type II, and 18.3% were coinfected with both. A statistically significant difference in antibody and bacteremia prevalences among geographical areas was detected. Statistical analysis showed no association between characteristics such as seroprevalence-bacteremic status, sex, general health status, and the presence of ectoparasites. The negative predictive value of serological test was 84.7%, and the positive predictive value was 31.8%. Receiving operator characteristic analysis of the data showed that serological tests had a low predictive value in relation to the bacteremic status of a cat; in surveys aimed at assessing the real risk of B. henselae infection in a human population, therefore, we suggest the use of blood culture as the reference test. Nevertheless, both blood culture assays and serological tests for Bartonella infection should be performed for a complete evaluation of the health status of cats.